Wildlife in the city: An innovative approach to urban design for playa lake parks in Lubbock, Texas - McCurley, Stephanie Shay (2001)
The prime objective ofthis study was to examine how people in Lubbock choose to interact with local wildlife so that guidelines which enhance people's experiences with urban wildlife can be developed. This thesis documented the behavior, reactions, and interactions of people towards wildlife during the winter months at three urban parks in Lubbock, Texas. The study was conducted at parks which contained modified playa lakes that provided year round water that is being utilized by wildlife. The time period for the site observations was dictated by the migration cycle ofthe Canada goose. Most ofthe behaviors documented were in relation to avifaima. Knowledge of wildlife habitats was combined with the study in Lubbock's parks to create proposed design guidelines that would enhance the experiences of those wishing to interact with wildlife. The proposed guidelines include two categories: (1) general guidelines which are intended to be used to cormect and combine urban habitats, and (2) site specific guidelines are aimed at enhancing habitats for the wildlife as well as to provide site elements that would increase human enjoyment One Lubbock park was redesigned, in a schematic form, to illustrate the application of design guidelines to a specific site in urban setting. This thesis also includes a brief historical background ofthe wildlife in Texas, the benefits of nature to human well-being, how wildlife fits into the urban scheme, as well as the role of landscape architects in providing urban wildlife habitats.